Liquid Chromatography Single Quadrupole Mass Spectrometry (LC/SQ MS) Analysis Reveals Presence of Novel Antineoplastic Metabolites in Ethanolic Extracts of Fruits and Leaves of Annona muricata - Gavamukulya, Yahaya; Maina, Esther N.; Meroka, Amos M.; Madivoli, Edwin S.; El-Shemy, Hany A.; Magoma, Gabriel; Wamunyokoli, Fred (Pharmacognosy Journal, 2019)
Annona muricata, a tropical plant species belonging to family Annonaceae is one of the most used plants in folk medicine because of its many medicinal uses. Despite its wide usage, there is still need to continue scientifically evaluating its medicinal properties in order to avoid any adverse effects. Elucidating the detailed chemical composition of this plant is a significant step towards this evaluation. Objective: The aim of this study was to conduct LC MS analysis on the ethanolic extracts of fruits and leaves of Annona muricata for detection of novel metabolites. Materials and Methods: Leaves and fruits of Annona muricata were collected from Eastern Uganda during the month January 2018. Extraction was conducted using the tissue homogenization method and the extracts were analyzed on an LC/SQ MS detection system. The results were obtained by analyzing the MS spectra using the retentions time and fragmentation patterns on the NIST Library. Results: The study revealed that the fruits extracts contain 1,3-Dimethylthiourea and (4-chlorophenyl)-[4-(3-chlorophenyl)-2-[(Z)-3-(dimethylamino) prop-1-enyl]quinolin-6-yl]-(3-methylimidazol-4-yl)methanol, which are reported antioxidant and antineoplastic agents. The leaves contained 2,4,6-Tribromoaniline another antioxidant and antineoplastic agent, while compound (dichlorozirconium(2+);dimethyl-bis(2-methyl-4- phenylinden-1-id-1-yl)silane was found in both extracts of fruits and leaves. Conclusion: The current study suggests that ethanolic extracts of fruits and leaves of Annona muricata contain compounds which are potent antioxidant, antineoplastic and therapeutic agents for various conditions and paves the way for the development of several treatment regimens from these plant parts. Finally, the compounds reported in this study have been identified for the first time as being found in Annona muricata.
Keywords: Annona muricata; Ethanolic extracts; Phytochemicals; LC/SQ MS; Antioxidant; Antineoplastic